The effect of polymorphic inversions on body size in two natural populations of Drosophila buzzatii from Argentina - Fanara, J.J. (1997)
Previous works in a colonized and an original population of Drosophila buzzatii have shown a consistent relationship between the inversion polymorphism and thorax length, a measure of body size. However, the populations studied in those reports share a close genealogical relationship as suggested by several lines of evidence. In the present paper, we revisit this issue by analysing the correlation between second chromosome arrangements and thorax length in two Argentinian natural populations (Termas de Rio Hondo and Arroyo Escobar) from different biogeographic areas with different host plants. Our findings are: (1) inversion frequencies were significantly different between populations; (2) the mean thorax length of flies collected in both populations was not significantly different; and (3) we obtain confirming evidence that flies carrying 2st, the ancestral gene order, have on average a smaller body size than those carrying the derived arrangements (2j and 2jz3). These results suggest that the biometrical effect of inversions on body size previously described are due to genetic differences between arrangements and not to the close historical relationship between the populations studied in previous reports.